The Formation of the Secondary Vocational Education System in the Turkestan Region during the Second Half of the 19th - Early 20th Centurу - Qodirov, Najmiddin Nematovich (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
The author examines the formation of the secondary vocational education system in the Turkestan region during the period of the first Russian modernization. They identify factors that, on the one hand, stimulated the development of education in new territory that became part of the Russian state, and, that on the other hand, hindered the training of local specialists. First of all, they take also into account the interest of the Russian administration in the modernization and incorporation of the region, one of the tools of which was educational policy. The emergence of various enterprises and cultural institutions in the region also generated a need for specialists who largely determined the direction of its development. At the same time, the preserved national traditions, interests of the clergy, and activities of local religious schools stood in the way of training specialists, especially those recruited from among the indigenous population. The source base of the study includes documents, stored in the Central State Archive of the Republic of Uzbekistan, reports and reviews of schools, regions, and departments of the Governorate General, reference and memorandum books of regional boards, as well as materials from the regional periodical press. The author identifies several stages in the creation of the educational system in the Turkestan region, determines the range of educational institutions, opened by the Russian authorities, and examines the results of their activities. The author comes to the conclusion that professional educational institutions, being a completely new experience for the local population, did not attract significant attention from the indigenous peoples. This was due, among other things, to a language barrier and insufficient adaptation of curricula to local conditions. The shortage of experienced teachers and limited funding for the education system also had a negative impact. Nevertheless, the professional schools that were created, especially in the field of agriculture, had a positive impact both on the development of the region’s economy and on the training of personnel that both the authorities and the indigenous population urgently needed.